The Relationship between Social Interaction and Family Support to the Quality of Life of the Elderly - Saraswasta, I Wayan Gede; Insani, Sahara Nurul (GLOBAL HEALTH SCIENCE GROUP, 2024)
In 2045, it is estimated that the population growth rate will enter the Super Aged Society category with the number of elderly ≥ 21% of the total population. This is a challenge because in general the elderly face weaknesses, limitations and inabilities. One of the things that needs to be considered is the quality of life of the elderly. Objective: To identify the relationship between social interaction and family support on the quality of life of the elderly. Methods: Quantitative research design with a cross-sectional data collection approach. The population in this study is all elderly people aged 60 years and above in Jogjogan Village, Bogor. The sampling technique uses purposive sampling with a sample of 92 people. The research has been carried out from February to June 2024. Data collection was carried out using questionnaires and observations. Data analysis uses a computerized process with a static test, namely the chi-square test. Results: The social interaction of the elderly was in the good category (30.4%), family support in the supportive category (53.3%) and the quality of life of the elderly was in the good category (60.9%). The results of the bivariate test showed a significant relationship between social interaction and quality of life (p-value: 0.00), and the relationship between family support and quality of life (p-value: 0.020). Conclusion: Social interaction and family support provided to the elderly are significantly related to the quality of life of the elderly.